AWARENESS OF MEDICAL APPLICATIONS OF MODAFINIL THERAPY AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Modafinil had initially evolved by a French neurophysiologist Professor Michel Jouvet. Modafinil started with the late 1970s creation of a progression of benzhydryl sulfinyl mixes, including adrafinil that was used in the management of narcolepsy in 1986. Modafinil is fundamentally utilized for its antisomnic function. The aim of the survey is for assessing the awareness of medical applications of Modafinil therapy amongst dental students. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about Modafinil therapy in medical applications, their medicinal uses, antisomnic activity, mechanism of action and side effects. The responses were recorded and analysed.94 % of the respondents were not aware of medical uses of Modafinil therapy .83 % were not aware of antisomnic activity therapy.90 % were not aware of the mechanism of action of Modafinil therapy .85% were not aware of side effects of Modafinil therapy. The awareness about the use of Modafinil therapy in medical applications is very less among dental students. Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications should be incorporated to improve the awareness levels.